Commercial flooring in Singapore. - Lee, Kok Yan. (2008)
This report aims to present the findings of our market research on the consumer needs in the carpet industry. The objectives are to understand the decision making process of buying carpet, the selection criteria of buying flooring in general and carpet, the type of maintenance usually done and problems participants face when using carpet.